Aplikasi ekstrak sarang semut sebagai senyawa antimikroba dan antioksidan pada permen karet herbal [Application of ant nests (Myrmecodia sp.) extract as antimicrobial and antioxidant compounds in herbal gum] - Nadra Khairiah; I Dewa Gede Putra Prabawa; Saibatul Hamdi; Nazarni Rahmi (Jurnal Riset Industri Hasil Hutan, 2019)
Ant nests (Myrmecodia sp.) are one of the medicinal plants that have many benefits for health. Ant nests are widely used as antimoicrobial, antidiabetic, anticancer and antiimplantation because ant nests usually contains chemical compounds such as flavonoids, terpenoids, saponins and polyphenol tannins. Flavonoids can be used as antioxidants, antiangiogenic, and antimicrobials. Many products can be developed from the extract, such as tea, powder and ant nest capsules. Another product innovation that needs to be developed is gum. It is important to conduct research to determine the optimum formulation of ant nest extract as an additional ingredient on candy products (gum). This study aims to determine the antimicrobial and antioxidant activities of ant nests extract and maximize the use of ant nest extractas at additional raw material for high quality gum. The ant nests were extracted using 70% ethanol. The concentrated extract was tested for antimicrobial activity in four types of pathogenic bacteriaEscherichia coli ATCC 25922, Staphylococcus aureus ATCC 6538, Streptococcus mutans ATCC 25175, Pseudomonas aeruginosa ATCC 9027, and Salmonella typhimurium ATCC 14028); antimicrobial positive control was tested using chloromphenicol and antioxidant activity positive control was tested with ascorbic acid (vitamin C). Dried ant nest extract was added to the gum mixture as much as 0.15% and 3% and then the quality was tested based on the parameters according to the quality standard of gum. The results of this study showed that ant nest extract had effective antibacterial activity in gram-positive and gram negative bacteria with an inhibitory zone of 10-13.5 mm. The high antioxidant activity of ant nests (85.90%) proven that ant nests had the potential as an natural antioxidants added in food. The addition of 0.15% and 0.3% extracts in chewing gum generally produced gum that met the quality standards of chewing gum, although the moisture content was slightly higher than the maximum limit of the standards.